Fine‐scale spatial genetic structure, mating, and gene dispersal patterns in Parkia biglobosa populations with different levels of habitat fragmentation - Lompo, Djingdia; Vinceti, Barbara; Konrad, Heino; Duminil, Jérôme; Geburek, Thomas (Wiley, 2020)
A good understanding of genetic variation and gene dispersal in tree populations is crucial for their sustainable management, particularly in a context of rapid environmental changes. West African Sudanian savannahs are being fragmented and degraded, partly due to expansion of crop cultivation and monocultures that reduce tree density and may impact pollinators. The population dynamics of important indigenous trees could also be affected. We investigated the influence of habitat fragmentation on patterns of genetic diversity and gene dispersal of a key Sudanian agroforestry tree species, Parkia biglobosa.Using 10 highly polymorphic nuclear microsatellites, we genotyped 2475 samples from reproductive trees, seedlings, and embryos in four tree populations presenting different levels of habitat fragmentation.Parkia biglobosa presented similar high genetic diversity across the four populations studied. Genetic diversity and inbreeding were similar between adults and embryo cohorts. In all four populations, the selfing rate was less than 1%. The effective number of pollen donors per tree was high (NEP~ 18–22), as was the pollen immigration rate (from 34 to 74%). Pollen dispersal was characterized by a fat‐tailed distribution with mean estimates exceeding 200 m. In three populations, stem diameter had a pronounced effect on male reproductive success. Here, the highest male reproductive success was observed in trees with a diameter at breast height between 60 and 75 cm.At the scale analyzed, fragmentation does not seem to pose limitations to gene flow in any of the sites investigated, regardless of the landscape configuration associated with the different tree stands. The study provides useful insights on the reproductive biology of an important tree species in the West African savannahs.